2006
DOI: 10.1111/j.1365-2036.2006.02753.x
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term prognosis in Crohn's disease: factors that affect quality of life

Abstract: SUMMARY BackgroundThere are many studies investigating quality of life in recently diagnosed patients and following surgery for Crohn's disease, but there are none investigating quality of life changes with disease duration. The response shift model suggests quality of life improves with time following diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
44
2
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(50 citation statements)
references
References 16 publications
(37 reference statements)
3
44
2
1
Order By: Relevance
“…Previous research suggests that increased disease severity is associated with poor adjustment in people with IBD (Canavan, Abrams, Hawethorne, Drossmans, & Mayberry, 2006;Sainsbury & Heatley, 2005), therefore, we proposed that disease severity will directly influence psychological adjustment.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research suggests that increased disease severity is associated with poor adjustment in people with IBD (Canavan, Abrams, Hawethorne, Drossmans, & Mayberry, 2006;Sainsbury & Heatley, 2005), therefore, we proposed that disease severity will directly influence psychological adjustment.…”
Section: Introductionmentioning
confidence: 99%
“…IBD often leads to feelings of shame, embarrassment and isolation, concerns regarding the risk of relapsing or developing cancer, difficulty in maintaining daily routines due to severe symptomatology that may arise abruptly, and struggles with body dissatisfaction and sexuality [4][5][6][7][8]. It has been reported that, even during periods of remission, IBD patients' QoL is significantly poorer in comparison with healthy controls, and that comorbid psychopathology is frequent [1,9,10].…”
Section: Inflammatory Bowel Disease and Psychological Distressmentioning
confidence: 99%
“…Predisposing factors for small bowel cancer are Crohn disease, with a relative risk (RR) of 33.0 (95% CI, 15-60.9) (Canavan et al, 2006). A recent meta-analysis demonstrated that the RR for individuals consuming the highest versus lowest category of alcohol intake was 1.51 (95% CI, 0.83-2.75).…”
Section: Introductionmentioning
confidence: 99%